Identification of Disabilities in Spanish-Speaking Children in English-Speaking Contexts - Francis, David J.; Santi, Kristi L.; Khalaf, Shiva; Bunta, Ferenc; Roja, Raul; Gusewski, Svenja; Hiebert, Lindsey (All about Language: Science, Theory, and Practice, 2019)
Keywords: dept.cmd

Speaking and Reading in Two Languages: On the Identification of Reading and Language Disabilities in Spanish-Speaking English Learners - Francis, David J.; Rojas, Raúl; Gusewski, Svenja; Santi, Kristi L.; Khalaf, Shiva; Hiebert, Lindsey; Bunta, Ferenc (New Directions for Child and Adolescent Development, 2019)
Articles in this issue examine (1) the primary sources of variability in reading and language achievement among Spanish-speaking English learners (ELs) in the United States, (2) the extent to which poor performance at the end of grade 2 is identifiable in developmental trajectories beginning in kindergarten, (3) the relations among core reading constructs of phonological awareness and decoding in both English and Spanish and the factors that affect their relationship, (4) the performance of different approaches to identification and the factors that influence how well they work, as well as (5) the growing literature focused on intervention for reading problems in this population. This article examines the literature on language minority students and disability identification and analyzes a large-scale longitudinal dataset (>4,000 ELs; >15,000 observations) to systematically characterize and describe the oral language and reading development of Spanish-speaking children designated as ELs from kindergarten to second grade, considering a range of factors that may potentially contribute to that characterization and its relation to academic performance. This systematic characterization should facilitate the development of an empirical basis for a theoretically grounded framework of typical development in ELs in order to more precisely identify those children with language and learning disabilities.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/cad.20306
Keywords: dept.cmd; peer-reviewed